#MeToo Online Disclosures: A Survivor-Informed Approach to Open Science Practices and Ethical Use of Social Media Data. (December 2021) - O'Callaghan, Erin; Douglas, Hannah M.
With social media data widely available, researchers are increasingly incorporating tweets, posts, and blogs in their work. While easily accessible, the use of "public" posts raises important questions about the ethics of mining, storing, analyzing, and reporting publicly available social media data—especially when gathering sensitive information such as sexual violence disclosures. Online movements including #MeToo and #WhyIDidntReport emerged to shed light on gender-based violence. These movements generate large quantities of data with little consistency and oversight across research groups, disciplines, and review boards on data ethics. With the recent push in social science to publish data to open science databases, the concerns of feminist psychologists and ethical concerns of social media research with survivors have become more salient. In this article, we describe and address these ethical issues by reviewing existing social media sexual assault disclosure research and make concrete recommendations for authors seeking to use social media data. We also seek to address these ethical concerns by noting the work of some feminist researchers, but also by pushing researchers to do more for survivors through a survivor-informed approach to this research in an open science context. We propose four survivor-informed recommendations for research with this vulnerable population: (a) get input from survivors, (b) update ethics review boards, (c) maximize benefits to participants, and (d) utilize study-appropriate datasets with informed consent.